2014
DOI: 10.5468/ogs.2014.57.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic assisted adenomyomectomy using double flap method

Abstract: ObjectiveThe purpose of this study was to evaluate postoperative prognosis and progression in patients who received laparoscopic-assisted adenomyomectomy using the double flap method.MethodsThe pelvic cavity was explored by the conventional laparoscopic method, and drainage was achieved through a 5-mm trocar. After a small incision in the abdomen, the uterus was incised from the fundus to the upper cervical margin until exposing the endometrial cavity. Adenomyotic tissue was removed using a scalpel, scissors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
2
24
1
Order By: Relevance
“…Kishi et al treated 102 patients with adenomyosis who had a desire for pregnancy by laparoscopic adenomyomectomy using the conventional method, and the clinical pregnancy rates in women with age ≤39 years and ≥ 40 year were 41.3% and 3.7%, respectively [ 40 ]. In our study, 10 patients who wished to conceive after surgery did not want to have a pregnancy so far, because their age were relatively older, and they have had children, which is in agreement with the study of Kim et al [ 17 ]. Actually, our study and the study of Kim et al contain less infertility patients compared with the studies of Kishi et al and Saremi et al [ 17 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Kishi et al treated 102 patients with adenomyosis who had a desire for pregnancy by laparoscopic adenomyomectomy using the conventional method, and the clinical pregnancy rates in women with age ≤39 years and ≥ 40 year were 41.3% and 3.7%, respectively [ 40 ]. In our study, 10 patients who wished to conceive after surgery did not want to have a pregnancy so far, because their age were relatively older, and they have had children, which is in agreement with the study of Kim et al [ 17 ]. Actually, our study and the study of Kim et al contain less infertility patients compared with the studies of Kishi et al and Saremi et al [ 17 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is indicated that the surgical efficacy of laparoscopic adenomyomectomy for the treatment of diffuse uterine adenomyosis can decrease over time. Therefore, long-term drug therapy such as Mirena (or oral contraceptives) is recommeneded after adenomyomectomy for the treatment of diffuse uterine adenomyosis [ 17 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative conservative surgical treatment for women who prefer to preserve the uterus is adenomyomectomy via laparotomy or laparoscopy. This procedure effectively relieves dysmenorrhea and menorrhagia [6,7,8]. One recent study showed that postoperative GnRH agonist administration reduces the recurrence of symptoms such as menorrhagia or dysmenorrhea [9].…”
Section: Introductionmentioning
confidence: 99%